Association between pain and training in elite swimmers - Gustavo Antonio Meliscki; Luciana Zaranza Monteiro; Carlos Alberto Giglio (Universidade de Fortaleza, 2011)
Objective: To determine whether there is an association between pain and training among elite swimmers. Methods: We assessed 42 athletes (22 men and 20 women) of an elite swimming team from the University of Ribeirao Preto in January 2010, aged 13 to 28 years, with a period of practice of at least three years, regarding anthropometric aspects, swimming training and the presence of pain. The anthropometric variables studied were: current weight, height and hip circumference. The results were statistically analyzed by Fisher exact test and Wilcoxon test using the SAS® 9 software. Results: Both men and women trained at the same frequency (6 x per week, for 2 hours). We did not observe significant associations between pain and training frequency for both genders. Regarding the presence of pain, 10 (50%) women referred it, being 30% low back pain and 20% at shoulder. Among men, 07 (31.8%) presented pain, of which 20% referred at shoulder and 11.8 % lower back pain. Conclusion: There was no association between pain and training, although the study highlighted the high number of swimmers with pain at shoulder and lower back